Annunciation As Election - Work, Telford 1965- (2001)
In his review of the historical tradition, James McClendon concludes that ‘the doctrine of election or predestination in Scripture viewed as a whole seems fully to warrant none of the paths ecclesiastical doctrine has so far taken’. He finds some hopeful signs, particularly in his own Radical Reformation tradition. Yet his redrawn contours of the doctrine rarely appeal to the tradition so far. ‘The old associations of the doctrine die so hard that (in my judgment) this part of Christian teaching is of litde present service. We do well to emphasize the rule of God in every effective way, while exercising great reserve with regard to this Augustinian deposit’.